Influence of Exercise on Platelet Function in Patients with Cardiovascular Disease - Hvas, Anne-Mette; Neergaard-Petersen, Søs (Seminars in Thrombosis and Hemostasis, 2018)
Regular exercise may reduce the risk of major cardiovascular thrombotic events. However, previous studies suggest that the risk of myocardial infarction or primary cardiac arrest is transiently increased during exercise. Thus, on the one hand, exercise seems to be able to protect against cardiovascular disease, but on the other hand, it seems to provoke sudden cardiac death. As platelets play a key role in arterial thromboembolic disease, the effect of exercise on platelet function is of special interest. This systematic review summarizes the evidence of the influence of exercise on platelet function in patients with coronary artery disease, angina pectoris, hypertension, or peripheral arterial disease. We specifically investigated, (1) if platelet function was increased in patients prior to exercise compared with healthy controls, (2) if exercise influenced platelet function differently in patients compared with healthy controls, and finally (3) if exercise reduced the effect of aspirin (acetylsalicylic acid). We performed a literature search in PubMed, Embase, Scopus, and Cochrane Library. In total, 18 articles were included and grouped into studies including patients with coronary artery disease (n = 7), angina pectoris (n = 5), hypertension (n = 5), and patients with peripheral arterial disease (n = 2). One study included both patients with coronary artery disease and patients with hypertension, and this study was therefore included in both groups. All studies performed short-term exercise either using treadmill (n = 12), primarily following the Bruce protocol, or bicycle ergometer test (n = 6). Overall, patients did not differ from healthy controls in platelet aggregation or activation prior to exercise. After exercise, conflicting results were reported with some studies reporting intensified platelet aggregation and/or platelet activation, some studies found no difference, whereas a few studies reported a reduction in platelet aggregation after exercise when compared with controls. Exercise seemed to impair the effect of aspirin during or shortly after exercise. In conclusion, the studies reported contradictive results. However, this review indicates that strenuous short-term exercise induces increased platelet activation also implying a reduced effect of aspirin during short-term exercise. Controlled studies on the effect of regular long-term low-intensity exercise are needed to further clarify the influence of long-term exercise on platelet function.
Keywords: blood platelets; platelet function tests; platelet activation; exercise